Engaging Australian healthcare consumers to determine priorities and consensus for precision medicine approaches to detect non-communicable disease in early life: a modified Delphi study - Tegan Grace; Kirsty Pringle; Craig Pennell; Samantha Hoskins; Gillian Mason; Melinda Cruz Turner; Keren Ludski; Leila Usher; Nafiseh Ghafournia (BMJ Open)
Objectives Research to develop early screening tools to determine an individual’s risk of developing adult-onset disease is a growing field. Expectant parents may find themselves with an option in the future to undergo screening to determine not only genetic abnormalities in their child but also their risk of developing adult-onset non-communicable diseases (NCD) such as hypertension, obesity or hypercholesterolaemia. To ensure acceptability and feasibility of new screening tools researchers must work in partnership with healthcare consumers to discern consumers’ current understanding and acceptance of these technologies in research and the potential for clinical applications. We sought to engage with healthcare consumers to develop a consensus, using a modified Delphi study design, for the acceptability of (1) screening tools for use within pregnancy that would indicate a child’s risk for developing NCD, and (2) targeted early interventions for those identified at a higher risk of developing NCD using precision medicine approaches. The acceptability of future research design and conduct as well as the implications for implementation into routine healthcare were discussed. In addition, participants were asked to rank the non-communicable diseases they believed were of most importance for precision medicine research focus, in line with recent calls for better involvement of healthcare consumers in setting research questions and defining priority areas.Design A modified two-stage Delphi study design including an in-person consumer workshop (stage 1) and online follow-up survey (stage 2), was used to evaluate consumer consensus for research to develop precision medicine tools for early detection and potential intervention to reduce onset of NCDs. The acceptability of research design and conduct and future implications for the implementation of newly developed tools into routine healthcare was also addressed.Setting and participants We engaged 76 healthcare consumers in 2020, in the Hunter New England Region, New South Wales, Australia. Participants were recruited from existing healthcare consumer organisations, research programmes and healthcare networks through purposeful selection, with a focus on participants having a broad range of experiences and backgrounds to ensure adequate representativeness.Results and conclusions Our findings indicate the majority (98%) of participants in our study believe early screening for risk of NCD in their children was acceptable, provided it was equitable and clear pathways for referral and support were available.